THE ASSOCIATION OF SUBJECTIVE AGE AND FINANCIAL EXPLOITATION RISK: SOCIAL SUPPORT AS A MODERATOR. (20th December 2022) - Weissberger, Gali; Bergman, Yoav
Abstract: Financial exploitation of older adults bears detrimental physical and psychological consequences. However, little is known regarding factors which may contribute to financial exploitation vulnerability (FEV) among this age-group. In line with the growing awareness of the importance of subjective perceptions of the aging process for older adults' functioning and well-being, the current work examined the connection between subjective age (i.e., feeling younger/older than one's chronological age) and FEV, and the possible moderating role of social support on this connection. Data were collected from a convenience sample of 137 Israeli older adults (age range 60-89, M=69.90, SD=6.85, 40.1% male), who completed scales assessing FEV, subjective age, and social support, as well as relevant socio-demographic information. Associations were examined using a hierarchical linear regression model which adjusted for age, sex, education, marital status, and self-rated economic and health status. The main effect of subjective age was not significant (B=1.24, p=0.14), while the main effect of social support was found (B=-1.30, p=.03) indicating that low levels of support were associated with increased FEV, a finding consistent with the literature. The interaction of social support × subjective age was significant (B= -1.17, p= .025), accounting for an additional 4.0% of variance. Older subjective age was associated with increased financial exploitation vulnerability when social support was low, but not when social support was high. Results are interpreted with regard to Socio-Emotional Selectivity Theory and provide initial information pertaining to the relevance of subjective age perceptions to FEV in older adults.